Pengaruh Waktu Milling Terhadap Mikrostruktur dan Sifat Magnetik Komposit NiFe2O4-NdFeO3 [Influence Of Milling Time on Microstructure and Magnetic Properties of NiFe2O4-NdFeO3 Composite] - Mulyawan, Ade; Yunasfi, Yunasfi; Adi, Wisnu Ari (Metalurgi, 2017)
The development of electromagnetic wave and microwave absorbing materials was important to overcome the electromagnetic wave interference in communication technology and in the development of radar materials for military purposes. In this study the composite which contained two different phases of NiFe2O4-NdFeO3 has successfully synthesized using Fe2O3, NiO, and Nd2O3 as starting materials through solid state reaction method. The composites were made by varying milling times from 10, 15, 20, and 25 hours then followed by sintering process at 1200 °C for 3 hours. Phase identification was performed using XRD (x-ray diffractometer) which revealed only NiFe2O4 and NdFeO3 phases. The crystallite size of the NiFe2O4 phase is in the range of 59-68 nm, and NdFeO3in the range of 62-65 nm. The agglomeration of particles was observed by using SEM (scanning electron microscope). Referring to the characterization result of the magnetic properties by using VSM (vibrating sample magnetometer), it is known that the parameters of the magnetic properties such as magnetization saturation (Ms), magnetization remanence (Mr), and coercivity (Hc) are highly dependent on the mass fraction, crystallite size,and the homogenity of the phase composition.AbstrakPengembangan bahan penyerap gelombang elektromagnetik dan gelombang mikro sangat penting dilakukan untuk mengatasi masalah interferensi gelombang elektromagnetik pada teknologi komunikasi serta pada material radar untuk tujuan militer. Pada penelitian ini berhasil dilakukan pembuatan material penyerap gelombang elektromagnetik komposit fasa NiFe2O4-NdFeO3 dengan menggunakan Fe2O3, NiO, dan Nd2O3 melalui reaksi padatan. Sampel komposit dimilling dengan variasi waktu 10, 15, 20, dan 25 jam dan selanjutnya disinter pada suhu 1200 oC selama 3 jam. Identifikasi fasa dilakukan dengan X-ray Diffractometer (XRD) menunjukan bahwa komposit hanya terdiri dari fasa NiFe2O4 dan NdFeO3. Ukuran kristalit fasa NiFe2O4 berada pada kisaran 59-68 nm, sedangkan fasa NdFeO3 pada kisaran 62-65 nm. Pengamatan morfologi permukaan dilakukan menggunakan Scanning Electron Microscope (SEM). Berdasarkan nilai parameter sifat magnetik yang dihasilkan menggunakan Vibrating Sample Magnetometer (VSM) seperti magnetisasi saturasi(Ms), magnetisasi remanen (Mr), dan koesivitas (Hc) sangat bergantung pada fraksi massa, ukuran kristalit, dan homogenitas fasa yang terbentuk.